Collaborative Growth: The Relationship between the Development Mode and the Profile of Moroccan SME - Echcharqy, Salma (International Review of Management and Marketing, 2020)
The purpose of this article is to study the relationship between the profile of Moroccan SMEs (Size, age, organizational structure, strategic orientation, etc.) and the use of collaborative growth when implementing strategic choices. To carry out this study, we first operationalize the key concepts of our research, namely: Collaborative growth and the profile of SMEs, then and through an empirical study on a sample of 100 Moroccan SMEs, we are trying to study the relationship between SMEs profile and their use of collaborative growth over the past three years (2019, 2018 and 2017). The results show that there is a statistically significant relationship between size, manager training, strategic direction and the use of collaborative growth. Keywords: Collaborative growth, SMEs, strategy implementation, development mode, alliance, JEL Classification: M100 DOI: https://doi.org/10.32479/irmm.10315